2010
DOI: 10.1371/journal.pone.0013657
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Mediates Hematopoietic Cell Expansion through Interleukin-6

Abstract: Parathyroid hormone (PTH) stimulates hematopoietic cells through mechanisms of action that remain elusive. Interleukin-6 (IL-6) is upregulated by PTH and stimulates hematopoiesis. The purpose of this investigation was to identify actions of PTH and IL-6 in hematopoietic cell expansion. Bone marrow cultures from C57B6 mice were treated with fms-like tyrosine kinase-3 ligand (Flt-3L), PTH, Flt-3L plus PTH, or vehicle control. Flt-3L alone increased adherent and non-adherent cells. PTH did not directly impact hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…IL-6 supports HPC proliferation, 28,29,58,59 and we have recently shown it to be a critical regulator of PTH actions in HPC expansion. 13 Because the calvarial organ is composed primarily of stromal osteoblastic cells, the predominant PPR-expressing cell population in the bone marrow, the more significantly increased PTH-induced IL-6 mRNA in Prg4 mutant calvaria suggests that a stromal osteoblastic cell is the target of PTH actions to modulate IL-6 and hematopoietic cells in the marrow of Prg4 mutant mice. Because PTH modulated other responsiveness genes similarly in both Prg4 mutant and wild-type mice, the heightened IL-6 regulation in Prg4 mutant mice points to the likelihood of a specific compensatory effect occurring with the loss of proteoglycan 4 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 supports HPC proliferation, 28,29,58,59 and we have recently shown it to be a critical regulator of PTH actions in HPC expansion. 13 Because the calvarial organ is composed primarily of stromal osteoblastic cells, the predominant PPR-expressing cell population in the bone marrow, the more significantly increased PTH-induced IL-6 mRNA in Prg4 mutant calvaria suggests that a stromal osteoblastic cell is the target of PTH actions to modulate IL-6 and hematopoietic cells in the marrow of Prg4 mutant mice. Because PTH modulated other responsiveness genes similarly in both Prg4 mutant and wild-type mice, the heightened IL-6 regulation in Prg4 mutant mice points to the likelihood of a specific compensatory effect occurring with the loss of proteoglycan 4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that intermittent PTH administration in normal mice supported hematopoiesis through actions on early HPCs. 2 Ex vivo and in vivo PTH studies by Pirih et al 13 using the global IL-6 knockout mouse model demonstrated that IL-6 supports PTH expansion of HPCs.…”
mentioning
confidence: 99%
“…PTH also supports the hematopoietic system by stimulating osteoblastic production of several cytokines, including IL-6 (7,8), CXCL12 (9), MCP-1 (also known as CCL2) (10,11), and the soluble IL-6 receptor (sIL6R) (4). PTH improved the success rate of hematopoietic stem cell (HSC) engraftment in hematopoietic malignancies and autoimmune diseases via supporting HSC repopulation of the marrow (12)(13)(14). The dependence of hematopoietic lineage cells for PTH anabolic actions is unknown.…”
mentioning
confidence: 99%
“…In mammals, endocrine signals can alter the tissue environment in the intestinal and hematopoietic SC niche (Calvi et al 2003) and can promote hematopoietic SC proliferation (Jung et al 2006;Adams et al 2007;Pirih et al 2010) and self-renewal (Nakada et al 2014). Additionally, endocrine hormones can regulate mammary gland development in part by directly altering mammary SC proliferation during puberty, pregnancy, and lactation (Asselin-Labat et al 2010;Joshi et al 2010) and epithelial cell fate during development (Wysolmerski et al 1998;Foley et al 2001).…”
mentioning
confidence: 99%